Integrative characterization of the near‐minimal bacterium Mesoplasma florum. Issue 12 (17th December 2020) - Matteau, Dominick; Lachance, Jean‐Christophe; Grenier, Frédéric; Gauthier, Samuel; Daubenspeck, James M; Dybvig, Kevin; Garneau, Daniel; Knight, Thomas F; Jacques, Pierre‐Étienne; Rodrigue, Sébastien
Abstract: The near‐minimal bacterium Mesoplasma florum is an interesting model for synthetic genomics and systems biology due to its small genome (~ 800 kb), fast growth rate, and lack of pathogenic potential. However, fundamental aspects of its biology remain largely unexplored. Here, we report a broad yet remarkably detailed characterization of M. florum by combining a wide variety of experimental approaches. We investigated several physical and physiological parameters of this bacterium, including cell size, growth kinetics, and biomass composition of the cell. We also performed the first genome‐wide analysis of its transcriptome and proteome, notably revealing a conserved promoter motif, the organization of transcription units, and the transcription and protein expression levels of all protein‐coding sequences. We converted gene transcription and expression levels into absolute molecular abundances using biomass quantification results, generating an unprecedented view of the M. florum cellular composition and functions. These characterization efforts provide a strong experimental foundation for the development of a genome‐scale model for M. florum and will guide future genome engineering endeavors in this simple organism. SYNOPSIS: A deep characterization of the near‐minimal bacterium M. florum reveals important features of this emerging model organism for systems and synthetic biology. Analysis of M. florum growth kinetics reveals four bacterial growth phases in rich medium, with a doubling time of ~ 32 min and an optimal growth temperature of 34°C. The most probable cell volume and cell mass are estimated through the integration of M. florum dry mass, cell diameter, and cell buoyant density into mathematical equations. Transcriptome profiling identifies a conserved promoter motif as well as a complex transcriptome architecture, with many intragenic promoters and overlapping transcription units. The absolute molecular abundance of RNA and protein species, including protein complexes such as ribosome and RNA polymerase are estimated. Abstract : A deep characterization of the near‐minimal bacterium M. florum reveals important features of this emerging model organism for systems and synthetic biology.